Analysis Correlation Study of Traffic Accident Characteristics on the Sungai Limau Road Section, Padang Pariaman Regency - Roza, Angelalia; Fitrayadi, Rahmat; Yusnita, Yessy (Universitas Negeri Padang, 2024)
Sungai Limau Highway Section, Padang Pariaman Regency Is an accident event that often occurs because this road section as a connecting route between the city of Pariaman and Agam regency and at the same time becomes a tourist spot adjacent to the coast causing a negative impact on public opinion and the security of private property, so as to suppress accidents, especially heavy accidents, The main factors causing accidents as well as knowing the relationship and impact on the severity of accidents need to be analyzed. This study aims to analyze the main causes and see the correlation relationship with the main factors that cause traffic accidents on the Limau river road, Padang Pariaman Regency. This study used data on the number of accidents that occurred in 2021, 2022, 2023 with a total of 95 accidents. The data analysis method used in this study is a correlation test to determine the linear relationship between each accident variable and the AEK (Accident Equivalent Number) technique for the examination of the most severe accidents. The results of the analysis showed that the main factors that resulted in traffic accidents on the Sungai Limau Road Section of Padang Pariaman Regency, namely drivers, most occurred on Mondays, often occurred at bright times from 06:00 to 19:00, vehicles were dominant motorcycles, and accidents often occurred in Kuranji Hilir. In the 2021-2023 time frame, the highest traffic level on the Sungai Limau road section of Padang Pariaman Regency occurred in 2022 with the equivalent number of accidents of 325.